2022
DOI: 10.1155/2022/4427804
|View full text |Cite
|
Sign up to set email alerts
|

Component Composition and Biological Activity of Various Extracts of Onosma gmelinii (Boraginaceae)

Abstract: Onosma roots are widely used in traditional medicine to treat various diseases throughout the world. In this study, for the first time, we investigated the component composition and biological activity of various extracts from the roots of Onosma gmelinii collected in the highlands of the Kakpakty Mountains of the Almaty region (Republic of Kazakhstan). Extracts were obtained by three different methods: percolation extraction, ultrasound-assisted extraction, and supercritical carbon dioxide extraction. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The current systematic review of the phytochemical contents of Onosma species presents major identified organic classes such as naphthoquinone (33), flavonoids (30), hydrocarbon (23), phenolic (22), ester (17), alkaloids (20), terpenoids (10), carboxylic acid (11), fatty acids (9), aromatics (12), and liganin (5) compounds as shown in Figure 4. In addition, miscellaneous chemicals such as 24,25-Dihydroxycholecalciferol, 5-hydroxymethyl-furoic acid, and uplandicine also enrich the diversity of the phytochemistry in Onosma plants.…”
Section: Chemical Profile Of Onosma Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…The current systematic review of the phytochemical contents of Onosma species presents major identified organic classes such as naphthoquinone (33), flavonoids (30), hydrocarbon (23), phenolic (22), ester (17), alkaloids (20), terpenoids (10), carboxylic acid (11), fatty acids (9), aromatics (12), and liganin (5) compounds as shown in Figure 4. In addition, miscellaneous chemicals such as 24,25-Dihydroxycholecalciferol, 5-hydroxymethyl-furoic acid, and uplandicine also enrich the diversity of the phytochemistry in Onosma plants.…”
Section: Chemical Profile Of Onosma Speciesmentioning
confidence: 99%
“…Some Onosma species have been well studied pharmacologically than others, and the most common ones are shown in Figure 1. The ethnobotanical and in vitro studies have revealed that most of this Onosma species has many medicinal capabilities such as sedatives [9], antioxidant [10], antiinflammatory [11], gastric disorders [11], antithrombotic [12], wound healing [13], Alzheimer [14], enzyme inhibitory [15], anti-tumor [16], anti-viral [17], antifungal [18], and COVID-19 curatives [19] (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O. L. species are primarily found in Asia, the Mediterranean region, Eurasia, and Europe, particularly in China, Iran, Syria, India, Turkey, Pakistan, and Sri Lanka [31][32][33][34]. Kumar et al [35] highlighted how distribution patterns of different O. L. species vary geographically.…”
Section: Geographical Distribution Of O Lmentioning
confidence: 99%
“…The literature review found that the genus O. L. has received relatively little attention in phytochemistry, with only a few reports of phenolic compounds, alkaloids, and naphthoquinones (Table 1) [33]. The plants of O. genus, have several categories of secondary metabolites like alkaloids, naphthazarins, aliphatic ketones, flavones lipids, phenolic compounds, and naphthoquinones (Figure 1) [34]. The naturally occurring isohexenylnaphthazarins alkannins and shikonins are chiral constituents primarily distributed in the outer layer of roots among several taxa belonging to the Boraginaceae family [51].…”
Section: Phytochemistrymentioning
confidence: 99%